The yeast rad18 mutator specifically increases G.C----T.A transversions without reducing correction of G-A or C-T mismatches to G.C pairs. - Kunz, B A (1991)
Inactivation of the Saccharomyces cerevisiae RAD18 gene confers a mutator phenotype. To determine the specificity of this effect, a collection of 212 spontaneous SUP4-o mutants arising in a rad18 strain was characterized by DNA sequencing. Comparison of the resulting mutational spectrum with that for an isogenic wild-type (RAD18) strain revealed that the rad18 mutator specifically enhanced the frequency of single base pair substitutions. Further analysis indicated that an increase in the frequency of G.C----T.A transversions accounted for the elevated SUP4-o mutation frequency. Thus, rad18 is the first eucaryotic mutator found to generate only a particular base pair substitution. The majority of G.C pairs that were not mutated in the rad18 background were at sites where G.C----T.A events can be detected in SUP4-o, suggesting that DNA sequence context influences the rad18 mutator effect. Transformation of heteroduplex plasmid DNAs into the two strains demonstrated that the rad18 mutator did not reduce the efficiency of correcting G-A or C-T mismatches to G.C pairs or preferentially correct the mismatches to A.T pairs. We propose that the RAD18 gene product might contribute to the fidelity of DNA replication in S. cerevisiae by involvement in a process that serves to limit the formation of G-A and C-T mismatches at template guanine and cytosine sites during DNA synthesis.